INSTANT RESULTS WITH LINGERING EFFECTS: HOW GOOGLE CAN BIAS OUR SOCIAL CONVERSATIONS - Muñoz-Bates Sarah (AoIR Selected Papers of Internet Research, 2015)
This study attempts to discover the ways in which Google can bias searchers into privileging one set of terms over the other, particularly in regards to undocumented immigration in the United States. Examining three standard functions of Google – (1) Google Autocomplete, (2) related search results, and (3) the actual results themselves – reveals how Google can shape society’s vocabulary (and therefore ideas) about immigration and undocumented immigrants. The study shows how Google often directs users toward the word illegal over the word undocumented and how this biasing can have negative repercussions in immigration discussions. I argue that the simple act of repeatedly displaying specific words or phrases holds the potential to influence how people research, learn, and discuss a specific topic, thereby shaping or constricting social conversation. My argument that Google searches – as an online activity – can play a role in informing people’s discussions around political issues expands upon separate research done by Zizi Papacharissi and Tatiana Tartarchevskiy on how people’s online activities can affect other areas of their lives. Developing these authors’ arguments to incorporate Google search activity represents the changing dynamic of how people currently use and interact with the Internet as a tool for enhancing or simplifying their lives.